Phosphate and Ammonium Removal from Wastewaters Using Natural-Based Innovative Bentonites Impacting on Resource Recovery and Circular Economy - Miltiadis Zamparas; Grigorios L. Kyriakopoulos; Marios Drosos; Vasilis C. Kapsalis (Molecules, 2021)
The research objective of the study is the estimation of a novel low-cost composite material f-MB (Fe-modified bentonite) as a P and N adsorbent from wastewaters. Τhe present study aimed at examining the phosphate and ammonium removal efficiency from different types of wastewater using f-MB, by conducting bench-scale batch experiments to investigate its equilibrium characteristics and kinetics. The SEM analysis revealed that the platelets of bentonite in f-MB do not form normal bentonite sheets, but they have been restructured in a more compact formation with a great porosity. Regarding the sorption efficiencies (Qm), the maximum phosphate sorption efficiencies (Qm) calculated using the Langmuir model were 24.54, 25.09, 26.13, 24.28, and 23.21 mg/g, respectively, for a pH range of 5 to 9. In addition, the maximum NH4+-N adsorption capacities (Qm) calculated from the Langmuir model were 131.8, 145.7, 168.5, 156.7, and 159.6 mg/g, respectively, for a pH range from 5 to 9. Another important finding of this study is that f-MB can recover P from treated wastewater impacting on resource recovery and circular economy (CE). The modified clay f-MB performed the phosphate and ammonium recovery rates of 80% and 78.5%, respectively. Finally, f-MB can slowly release the largest proportion of phosphate and ammonium ions for a long time, thus extending the application of the f-MB material as a slow-release fertilizer and soil improver.